The Effect of Corporate Governanceon Audit Report Timeliness in Indonesia - Darryl Lirungan; Senny Harindahyani (Jurnal Akuntansi Bisnis, 2018)
Financial Statements could be useful for the readers to make a decision. In order to rely on Financial Statements to make a decision, the Financial Statements should be relevant. To enhance the relevance of the Financial Statements, the Financial Statements should be published in a timely manner. This research utilizes the data of listed companies on the Indonesia Stock Exchange for period 2013 – 2016. The purpose of this research is to determine the effect of corporate (internal and external indicators) on audit report timeliness. The methodology used in this research is multiple linear regression. In conclusion, the result of this research suggested that board of commissionersindependence, audit committee size, audit committee meeting, firm performance, auditor type, and audit opinion have significant association with audit report timeliness. Meanwhile, audit committee qualification and audit tenure do not have significant association with audit report timeliness. In addition, the result suggested that audit tenure weaken the relationship between auditor type and audit report timeliness.